Evaluating the Mediating Role of HR Practices in Workplace Digitalization Using SmartPLS - Handra, Tessa; Malika, Najalia; Patricia Pasha, Lucy (APTISI Transactions on Management (ATM), 2025)
The rapid digitalization of workplaces has transformed organizational opera- tions, but the role of human resource (HR) practices in this process remains un- derexplored. Understanding how HR practices mediate the relationship between digitalization and organizational outcomes is crucial for maximizing the benefits of technological investments. This study aims to examine the mediating role of HR practices in workplace digitalization and its impact on organizational performance. Using a quantitative research design, data were collected through a structured survey of 300 HR professionals and managers across various in- dustries. Structural Equation Modeling (SEM) with SmartPLS was employed to analyze the relationships between workplace digitalization, HR practices, and organizational outcomes. The study tested hypotheses regarding the direct in- fluence of digitalization on HR practices and the mediating effect of HR in- terventions on organizational performance. Results indicate that workplace digitalization significantly and positively affects HR practices (path coefficient = 0.72, p < 0.001), and HR practices substantially mediate the relationship be- tween digitalization and organizational outcomes (indirect effect = 0.31). These findings highlight the critical role of HR strategies, such as targeted training and performance management, in leveraging digital transformation for improved or- ganizational effectiveness. The study concludes that aligning HR practices with digital initiatives is essential for realizing the full potential of workplace digitalization, contributing to both organizational success and broader Sustain- able Development Goals.